2016
DOI: 10.1039/c6ra09112a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of kesterite Cu2ZnSnTe4via ball-milling of elemental powder precursors

Abstract: Cu2ZnSnTe4 was synthesized using mechano-chemical route from its elemental precursors. A homologous series of kesterite light absorber material Cu2ZnSnX4 (X: S, Se, Te) can be used for realization of multi-junction solar cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…From EDS measurements, the relative atomic percentage of the constituent elements CZTTe thin film layer was obtained as Cu:Zn:Sn:Te = 13:10:21:56% by considering the expected experimental errors of about 1%. In figure 1, XRD measurement of the film sample on a glass substrate showed that the as-grown film layer is in a polycrystalline structure with the main orientation along the (112) plane direction [7,8]. As given in figure 1, the XRD pattern of the deposited film is consistent with the JCPDS cards 01-081-5256 and 01-081-7520, and also with the literature works which indicate the obtained CZTTe profile possibly in the kesterite phase [6,8].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…From EDS measurements, the relative atomic percentage of the constituent elements CZTTe thin film layer was obtained as Cu:Zn:Sn:Te = 13:10:21:56% by considering the expected experimental errors of about 1%. In figure 1, XRD measurement of the film sample on a glass substrate showed that the as-grown film layer is in a polycrystalline structure with the main orientation along the (112) plane direction [7,8]. As given in figure 1, the XRD pattern of the deposited film is consistent with the JCPDS cards 01-081-5256 and 01-081-7520, and also with the literature works which indicate the obtained CZTTe profile possibly in the kesterite phase [6,8].…”
Section: Resultsmentioning
confidence: 99%
“…In fact, among the Cu 2 ZnSnX 4 group of compounds, it was reported that the distribution of Cu, Zn and Sn can cause negligibly small differences in the material properties as band structures, electronic characteristics [9]. Experimentally, similar to S-and Se-based compounds, the structure of this new compound was reported with point group symmetry I42m and the lattice parameters of 0.6088 and 1.2180 nm [1,8].…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations